A Case Study into Junior School Teachers' Perspectives on Wellbeing. - O'Brien, Aisling (Marino Institute of Education, 2018)
The topic of wellbeing is currently a significant theme in educational research. It is clear from the literature that wellbeing is rarely explicitly defined due to its complex nature. However a person's wellbeing is something that must be protected in order to experience happiness and success in life. In terms of wellbeing and education, research suggests that there is a link between mental health, academic success and life opportunities and for this reason schools are seen to be crucial in promoting wellbeing. In this way, many Irish primary schools are now introducing the roll-out of specific wellbeing programmes to ensure that children are receiving emotional education from a young age. The FRIENDS for Life Programme, The Incredible Years Programmes and Zippy's Friends are examples of the latest evidence based intervention programmes that promote well-being in primary schools with a specific focus on resilience, childhood anxiety prevention and emotional wellbeing. This study investigates into the topic of wellbeing in junior primary schools. In particular, it explores junior school teachers' wellbeing perceptions and practices. The objectives of the research are to examine teacher's understanding and perspectives on the importance of wellbeing and to explore teachers' understanding of the support frameworks available to them on a programme or school basis and their attitudes to these. This particular piece of research endeavours to analyse teachers' perceptions of the role of parents in the development of children's wellbeing and to investigate the specific challenges of the development of wellbeing in junior primary schools. In addition, the role of formalised testing and the impact it can have on children's well-being is explored. This case study is located in the constructivist research paradigm. The research data finds that teachers feel responsible for the development of children's wellbeing in conjunction with children's parents. Participating teachers believe that a shared responsibility between teachers and parents is essential if children's holistic development is to be catered for. The interviewees recognise the need to teach emotional education but many feel under-resourced and underqualified to tackle it. Outside of the demands of the curriculum, participants report that children of junior school age require a vast amount of care and nurture and this can be emotionally and physically challenging for teachers. The data presents conflicting opinions on the impact of formalised testing in junior primary schools. The findings suggest that an emotional curriculum be introduced into primary schools and that teachers should be engaging in more continuous professional development in order to feel confident when teaching emotional education. Collaborative relationships between schools and parents should be treated with utmost respect and importance to support children's wellbeing. Overall, the results of this particular research emphasises the valuable role parents and teachers play in a child's life. As the research reminds us, academic achievement should not take precedence over a child's emotional development. Undeniably, safeguarding children's well-being is necessary for a successful and happy future.
Master in Education Studies (Early Childhood Education)
Keywords: Research Subject Categories; Wellbeing; Irish primary schools; Intervention programmes; Resilience; Childhood anxiety prevention; Mental health; Academic Success; Role of parents